Aspectos moleculares envolvidos na nefrotoxicidade induzida pela cisplatina - Estrela, Gabriel Rufino [UNIFESP] (2017)
Cisplatin is one of the antitumor agents most commonly used in chemotherapy, but nephrotoxicity is frequent and one of the limitations of its use. There are several mechanisms that contribute to renal dysfunction following exposure to cisplatin: direct tubular toxicity inducing apoptosis, necrosis and inflammation. Kinin B1 receptor is a receptor induced in inflammatory states, it is known that the increase of TNF-α and IL-1β, as well as the activation of NF-κB are able to regulate the expression of this receptor. Recently our group has shown that deletion and blockage of kinin B1 receptor is able to attenuate cisplatin-induced nephrotoxicity. It is known that clearance of cisplatin is primarily dependent on organic transporters, OCT-2 responsible for the transport of cisplatin into the renal epithelial cell and MATE-1, which is responsible for the extrusion of drug in renal cells. Several studies show that both physical exercise and caloric restriction are excellent tools to attenuate the inflammatory response, reducing apoptosis, cytokine expression, production of reactive oxygen species, increase of antioxidants and anti-inflammatory and anti-apoptotic mediators. Because both B1 receptor deletion and antagonism attenuates cisplatin-induced nephrotoxicity, we have examined whether this protection is due to modulation of influx and efflux of cisplatin into the renal cell. In addition, we used physical exercise and caloric restriction against cisplatin-induced nephrotoxicity to see if both tools are able to attenuate renal toxicity. Cisplatin decreases the expression of OCT-2 and MATE-1 in the kidneys, animals knockouts for the B1 receptor are able to preserve the expression of these transporters and present lower concentration of platinum in renal tissue. Moreover, we observed that both physical exercise and caloric restriction are able to attenuate cisplatin-induced nephrotoxicity, decreasing the expression of pro-inflammatory cytokines and apoptosis. Caloric restriction together with physical exercise increases the expression of PPAR-α, but only the restriction increases the expression of PPAR target genes. The combined treatment of caloric restriction with PPAR-α antagonism does not attenuate acute tubular necrosis, shows no decrease in TNF-α expression, and does not demonstrate a decrease in expression in genes related to intrinsic apoptosis. By this we showed that kinin B1 receptor has a role in nephrotoxicity induced by cisplatin and it is by part due to modulation of organic transporters and that some of benefical effects of caloric restriction is mediated by PPAR- α.